Efektifitas Penerapan Metode Pembelajaran Auditory Intellectualy Repetition (AIR) Terhadap Prestasi Belajar Matematika Siswa Kelas VII SMP Negeri 2 Kambowa - Maya Nurlita; Hartati Hartati (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Dayanu Ikhsanuddin, 2021)
The purpose of this study was to dertermine the effectiveness of the application of the Auditory Intellectually Repetition (AIR) model on the learning achievenment of grade VII students of SMP Negeri 2 Kambowa Buton Utara Regency.This study was a quantitative reseacrch and used quasi-experimental research. The Population in this study were students of VII grade at SMP Negeri 2 Kambowa North Buton Regency as many as 40 students. The sample in this study were 20 students of class VII A and 20 students of VII B. The sampling technique used rondom sampling tecthique. The instruments used in this study were observation sheets and tests. The research results obtained: 1) the average value using the Auditory Intellectually learning model except Repetition (AIR) was 64,50. 2 ) the average volue without using the Auditory Intellectually learning model except Repetition (AIR) is 60,75. From the results of hypothesis testing using the t-test, the value tcount = 0,746 was obtained. At the real level α = 0,05, the value of t table = 1,68595 was obtained with df = 38, this indicated that tcount < t table, sig (2-tailed at 0,461> 0,05, so that it could be concluded that Ho was accepted and HI was rejected. There was no difference between learning using the Auditory Intellectually with Repetition (AIR) learning model or it could be said that the ineffective application of the Auditory Intellectully and Repetition (AIR) learning model on the mathematics learning achievement of VII grade students of SMP Negeri 2 Kambowa.